A PSYCHOLOGICAL IMPACT TO AUDIENCE OF “ZOOTOPIA” FILM: READER RESPONSE CRITICISM - Rumini Rumini; Vera Magria; Dedi Efendi (Universitas Muara Bungo, 2018)
This research analyzes about response and impact psychology’s audience about the main characters in Zootopia film, Judy Hopps and Nick Wilde although they conflict use the psychological approach. The sources of data are the audience responses of “Zootopia” film with subtitle. The researcher uses Reader Response Criticism from Charless E. Bressler (1998) to find out the audience response of the main character. From the analysis it can be concluded according to Bressler (1998), every audiences will give a different perspective and reaction toward what they read, and it can be influenced by the audience’s experience. From those interpretation of all audiences, it can be explained that mostly of them have same interpretation of Nick and Judy’s conflict. It can be seen from how the audience reacted toward them actions and conflict differently. From the responses of Zootopia, the researcher get the psychology impacts to the audiences. The psychology impacts of Zootopia film are positive and negative impact. The positive of psychology impacts are Happiness, Inspiration, and Love. While, the negative of Psychology impact are Fear and Guilt. Keywords: Reader Response Criticism, Psychology Approach, Zootopia film